Metal–Organic Frameworks and Their Derivatives: Designing Principles and Advances toward Advanced Cathode Materials for Alkali Metal Ion Batteries. Issue 22 (18th March 2021) - Zhu, Wei; Li, Ang; Wang, Zhuanping; Yang, Jixing; Xu, Yunhua
Abstract: Metal−organic frameworks (MOFs) and their derivatives have attracted enormous attention in the field of energy storage, due to their high specific surface area, tunable structure, highly ordered pores, and uniform metal sites. Compared with the wide research of MOFs and their related materials on anode materials for alkali metal ion batteries, few works are on cathode materials. In this review, design principles for promoting the electrochemical performance of MOF‐related materials in terms of component/structure design, composite fabrication, and morphology engineering are presented. By summarizing the advancement of MOFs and their derivatives, Prussian blue and its analogs, and MOF surface coating, challenges and opportunities for future outlooks of MOF‐related cathode materials are discussed. Abstract : Metal–organic frameworks (MOFs) bring a new light to the development of cathode materials owing to their unique and designable porous structures and components. Here, the research advances on MOF‐related cathode materials in alkali metal ion batteries are summarized in terms of structure design, composite fabrication, and morphology engineering, providing a comprehensive guidance on designing high‐performance MOF‐related cathode materials.